The Future of the Lecture in Neurology Education - Schaefer, Sara M.; Dominguez, Moises; Moeller, Jeremy J. (Seminars in Neurology, 2018)
The lecture has been a core pedagogical method since the early days of formal medical education. Although approaches to formal lectures have evolved over the years, there has been ongoing debate about the role that lectures should play in modern medical education. Arguably, traditional lectures do not align well with modern learning theory, and do not take full advantage of our current knowledge of how people learn. In many modern medical curricula, lectures have been replaced by self-study activities, including video-based lectures, computer-based learning modules, and other self-directed learning. We argue that scheduled “together time” is still important, particularly in neurology education, where there is a strong emphasis on clinical reasoning. We outline alternative teaching methods that effectively use this time, including the flipped classroom, just-in-time teaching, problem-based learning, and team-based learning. We discuss ways in which these approaches may be particularly conducive to components of neurology education.
Keywords: lectures; flipped classroom; just-in-time teaching; neurology education